THE USE OF U-DICTIONARY APPS AS AN ENGLISH LEARNING MEDIA AT SMANEGERI 4 MAROS - Suhardi, Muhammad Farhan; Samtidar, Samtidar; Munir, Munir (Universitas Negeri Makassar, 2024)
This research aims to determine the use of U-Dictionary apps as an alternative strategy to improve students' vocabulary mastery in learning English, and also to determine students’ perceptions of using U-Dictionary Apps. This study adopted the quantitative method and used a pre-experimental approach with a total sample of 68 students, 35 students in the control class and 33 students in the experimental class at SMA Negeri 4 Maros. In this study, data collection was carried out by conducting pre-tests and post-tests. The results of the data analysis showed that the use of U-Dictionary Apps as a learning media can improve students' vocabulary mastery, and students give positive perceptions of the use of U-Dictionary Apps. This can be proven by the t-test value lower than P (0.000 < 0.05) which means that H0 of this study is rejected and H1 is accepted. So, it can be concluded that the use of U-Dictionary Apps can improve students' vocabulary in class XI at SMA Negeri 4 Maros.